Lactobacillus rhamnosus MP108 alleviates ulcerative colitis in mice by enhancing the intestinal barrier, inhibiting inflammation, and modulating gut microbiota - Huizhen Li; Yang Chen; Huiting Fang; Xinmei Guo; Xuecong Liu; Jianxin Zhao; Wei Chen; Bo Yang (Food Science and Human Wellness)
Ulcerative colitis (UC) is a long-term inflammatory disorder that has evolved into a worldwide challenge. The development of new therapies against UC is imperative as all current therapies for UC are flawed in some way. Thus, the present study aimed to assess the palliative effects of Lactobacillus rhamnosus MP108 on UC in mice and to explore its potential mechanisms. The results showed that L. rhamnosus MP108 ameliorated the symptoms of UC, including preventing body weight loss, disease activity index (DAI) elevation, and colon shortening, and attenuated colonic pathological damage. L. rhamnosus MP108 dramatically increased the number of goblet cells, MUC2 level, and tight junction protein level in the colon and remarkably inhibited epithelial cell apoptosis, thereby strengthening the intestinal barrier. L. rhamnosus MP108 pronouncedly diminished pro-inflammatory cytokine levels and strikingly augmented anti-inflammatory cytokine levels, in turn suppressing inflammation. Furthermore, L. rhamnosus MP108 conspicuously boosted the proportion of short-chain fatty acids (SCFAs) producers in gut microbiota, contributing to increased levels of acetate and butyrate. Therefore, L. rhamnosus MP108 might alleviate UC via improving the intestinal barrier, inhibiting inflammation, and modulating intestinal microbiota.